2017
DOI: 10.1038/srep41215
|View full text |Cite
|
Sign up to set email alerts
|

The green microalga Tetraselmis suecica reduces oxidative stress and induces repairing mechanisms in human cells

Abstract: Green microalgae contain many active pigments such as carotenoids having antioxidant and protective activity on human cells. Here we investigate the biological activity of an ethanol/water extract of the marine green microalga Tetraselmis suecica containing high levels of carotenoids such as the xanthophylls lutein, violaxanthin, neoxanthin, antheraxanthin and loroxanthin esters. This extract has a strong antioxidant and repairing activity in the human lung cancer cell line (A549) as shown by the increased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 30 publications
0
70
0
Order By: Relevance
“…For instance, previous studies reported that the antioxidant effects in cultured human fibroblasts, irradiated with UV-A light (20 J/cm 2 ), were enhanced when a combination of antioxidant compounds (with β-carotene, as the main component, α-tocopherol and ascorbic acid) was used as a treatment [ 50 ]. In addition, a mixture of β-carotene and vitamins E and C showed a stronger synergistic scavenging effect of the reactive nitrogen species than the single antioxidants [ 51 ].Recent investigations demonstrated that the green microalga Tetraselmis suecica is characterized by a natural pool of bioactive pigments (including neoxanthin, violaxanthin, antheraxanthin, lutein, α- and β-carotene) working synergistically against oxidative damage [ 52 ]. In particular, this pool of bioactive pigments showed scavenging activity (with DPPH assay) and repairing activity when the T. suecica crude extract was used as recovery treatment in human fibroblasts after pre-injury with H 2 O 2 (30 mM for 1 h).…”
Section: Biological Functions Of Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous studies reported that the antioxidant effects in cultured human fibroblasts, irradiated with UV-A light (20 J/cm 2 ), were enhanced when a combination of antioxidant compounds (with β-carotene, as the main component, α-tocopherol and ascorbic acid) was used as a treatment [ 50 ]. In addition, a mixture of β-carotene and vitamins E and C showed a stronger synergistic scavenging effect of the reactive nitrogen species than the single antioxidants [ 51 ].Recent investigations demonstrated that the green microalga Tetraselmis suecica is characterized by a natural pool of bioactive pigments (including neoxanthin, violaxanthin, antheraxanthin, lutein, α- and β-carotene) working synergistically against oxidative damage [ 52 ]. In particular, this pool of bioactive pigments showed scavenging activity (with DPPH assay) and repairing activity when the T. suecica crude extract was used as recovery treatment in human fibroblasts after pre-injury with H 2 O 2 (30 mM for 1 h).…”
Section: Biological Functions Of Carotenoidsmentioning
confidence: 99%
“…T. suecica is rich in tocopherol, carotenoids and chlorophyll and has been suggested as a food supplement in human and animal diets. The total carotenoids content of T. suecica exhibited antioxidant and repairing activity in human cell lines [ 52 ].…”
Section: Sources Of Carotenoids From Marine Organismsmentioning
confidence: 99%
“…Rasmussen and Morrissey (2007) presented an overview on the food ingredients produced by marine organisms, highlighting microalgae and/or their bioactive ingredients. In addition, Sansone et al (2017) recently presented that an extract obtained from the green microalga Tetraselmis suecica had a strong antioxidant and repairing activity in a human cancer cell line. On the other hand, bioactive molecules for cosmetic products are characterized by their capacity to stimulate beneficial properties or to interfere with pathways leading to skin damage (Krutmann, 2001;Yarosh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts for pigment analysis and biological assays were obtained from freeze-dried young and old leaves of H. stipulacea, according to Sansone et al (Sansone et al 2017) at room temperature, under dark and N 2 atmosphere to avoid oxidation during procedure. One g of leaves was placed in 1 ml of ethanol/water mixture (3/1; v/v) for 30 min in dark condition and mechanically disrupted with a pestle.…”
Section: Preparation Of Ethanol/water Extracts From Halophila Stipulamentioning
confidence: 99%